Bandgap tunable colloidal Cu-based ternary and quaternary chalcogenide nanosheets via partial cation exchange. Issue 15 (8th January 2016) - Ramasamy, Parthiban; Kim, Miri; Ra, Hyun-Soo; Kim, Jinkwon; Lee, Jong-Soo
Abstract : A simple and reproducible partial cation exchange approach has been reported for 2D colloidal Cu2 GeSe3, Cu2 ZnGeSe4 and their alloyed Cu2 GeS x Se3− x, Cu2 ZnGeS x Se4− x nanosheets. Abstract : Copper based ternary and quaternary semiconductor nanostructures are of great interest for the fabrication of low cost photovoltaics. Although well-developed syntheses are available for zero dimensional (0D) nanoparticles, colloidal synthesis of two dimensional (2D) nanosheets remains a big challenge. Here we report, for the first time, a simple and reproducible cation exchange approach for 2D colloidal Cu2 GeSe3, Cu2 ZnGeSe4 and their alloyed Cu2 GeS x Se3− x, Cu2 ZnGeS x Se4− x nanosheets using pre-synthesized Cu2 x Se nanosheets as a template. A mechanism for the formation of Cu2− x Se nanosheets has been studied in detail. In situ oxidation of Cu + ions to form a CuSe secondary phase facilitates the formation of Cu2− x Se NSs. The obtained ternary and quaternary nanosheets have average lateral size in micrometers and thickness less than 5 nm. This method is general and can be extended to produce other important ternary semiconductor nanosheets such as CuIn1− x Ga x Se2 . The optical band gap of these nanosheets is tuned from 1 to 1.48 eV, depending on their composition.